Long‐term outcome of dogs recovering from acute kidney injury: 132 cases. (28th April 2022) - Bar‐Nathan, Mali; Chen, Hilla; Rimer, Dar; Segev, Gilad
Abstract: Background: Information regarding long‐term outcome of dogs recovering from acute kidney injury (AKI) is limited. Objectives: Determine the long‐term outcome of dogs recovering from AKI and identify predictors for serum creatinine concentration (sCr) normalization and long‐term outcome. Animals: One hundred thirty‐two dogs with AKI that survived ≥30 days postdischarge. Methods: Retrospective study. Search of medical records of dogs diagnosed with AKI that survived to discharge. Follow‐up data were retrieved from medical records and by telephone interviews with the owners or primary care veterinarians or both. Results: Estimated median survival time (MST) was 1322 days (95% confidence interval [CI], 1147‐1626), and 76% of the dogs were alive at last contact. Normalization of sCr was documented in 55% of the dogs at discharge and in additional 20% during the follow‐up period. The proportion of dogs with sCr normalization decreased with increase in AKI grade ( P = .02). Long‐term survival was not associated with sCr normalization ( P = .63). Etiology was associated with the long‐term outcome ( P = .004). Conclusion and Clinical Importance: Long‐term survival of dogs with AKI is longer than previously described. Normalization of sCr in 99 dogs (75%) occurred, either at discharge or within the follow‐up period. Normalization of sCr was not associated with long‐term survival. Estimated MST of dogs with sCr normalization was not different compared with dogs that developed azotemic chronic kidney disease (CKD), presumably because of slow CKD progression rate. Etiology is an important factor determining sCr normalization and long‐term survival, emphasizing the importance of the reversibility of renal injury rather than its severity.